Prime Minister Decree No. 2259 of the year 2015 concerning the amendment of the sale prices of the electric energy and customer service charge of the year 2015/2016 = قرار رئيس مجلس الوزراء رقم 2259 لسنة 2015 بشأن تعديل أسعار بيع الطاقة الكهربائية ومقابل خدمة العملاء لعام 2015/2016 / Prime Minister. - Egypt. Prime Minister. (2025)
Prime Minister Decree no. 2259 of the year 2015 concerning the amendment of the sale prices of the electric energy and customer service charge of the year 2015/2016 قرار رئيس مجلس الوزراء رقم 2259 لسنة 2015 بشأن تعديل أسعار بيع الطاقة الكهربائية ومقابل خدمة العملاء لعام 2015/2016